(untitled) (AYUSHDHARA, 2025)
Psoriasis is an autoimmune skin disorder characterized by dry, scaly patches and inflammation, often exacerbated by environmental factors, stress, and local injuries. Ayurveda, addresses psoriasis as a result of Tridosha imbalance, particularly the vitiation of Pitta and Kapha, alongside the involvement of Raktadhatu and Mamsadhatu. The disease is managed through a holistic approach, combining Sodhana (purification therapy) and Shamana (palliative therapy). In this case, a 21-year-old male patient presented with symptoms of scaly, reddish-black patches along with itching and burning on the whole body for one year. After clinical examination and diagnosis of Ekakushtha (psoriasis), a tailored Ayurvedic treatment protocol was implemented, integrating Panchakarma therapies and internal medicines. Key interventions included Deepana (digestive stimulation) with Panchkola Churna along with Takradhara, Snehpana (internal oleation) with Murchchita Goghrita, followed by Vamana Karma (emesis) and Virechana (purgation) followed by Samsarjana Krama. The treatment was complemented by oral medications and oil for local application. Over a period of 90 days, significant clinical improvements were observed, with reduced itching, burning, and scaling, leading to complete recovery. The patient showed no recurrence of symptoms, demonstrating the efficacy of this multimodal Ayurvedic approach. This case highlights the potential of Ayurveda to manage chronic, autoimmune conditions like psoriasis by addressing the root causes of the disease, offering long-term relief and improved quality of life. Further research is needed to validate these findings and explore the broader applicability of Ayurvedic treatments for chronic inflammatory skin diseases.